A scheduling framework for heterogenous multiprocessor architectures based on industrial processors (DSP and microcontrollers) - Tavares, Adriano (2001)
Current VLSI and networking technology, the increase in computational power, and the rapid decrease in computational cost, enable the interconnection of VLSI processors, which can be arranged on a functional decomposition of the computational task to exploit the potential of multiprocessing. The use of multiprocessor systems in such way, provides a novel and cost effective solution in solving many practical problems in signal processing, control systems, instrumentation systems and robotics. In this article we present a framework that addresses the specificities of industrial processors, such as DSPs and microcontrollers and can easily be used to implement a huge range of scheduling algorithms.